2009
DOI: 10.1017/s1755267209001134
|View full text |Cite
|
Sign up to set email alerts
|

Indo-Pacific cardinal fish in the Mediterranean Sea—new records of Apogon smithi from Turkey and A. queketti from Israel

Abstract: The present paper reports new records of Apogon smithi in Turkey and A. queketti in Israel and raises the subject of the newly emerging pattern of nearly simultaneous appearance of new Indo-Pacific records along the entire Levantine coast of the Mediterranean Sea. A key to the species of Apogon in the Mediterranean is supplied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 21 publications
0
13
0
1
Order By: Relevance
“…Ventral fins with a spine and 5 rays. The first report for Apogon queketti from the Mediterranean Sea was from øskenderun Bay (Turkey) by ERYILMAZ & DALYAN (2006), and the second, at depths of 20-70 m on sandymud and muddy bottoms, from Israeli Mediterranean shores by GOREN et al (2009). We found A. queketti at depths of 140-150 m on sandy-mud and muddy bottoms.…”
mentioning
confidence: 51%
“…Ventral fins with a spine and 5 rays. The first report for Apogon queketti from the Mediterranean Sea was from øskenderun Bay (Turkey) by ERYILMAZ & DALYAN (2006), and the second, at depths of 20-70 m on sandymud and muddy bottoms, from Israeli Mediterranean shores by GOREN et al (2009). We found A. queketti at depths of 140-150 m on sandy-mud and muddy bottoms.…”
mentioning
confidence: 51%
“…It is likely that M. affinis juveniles, commonly found in reduced salinity habitats in shallow waters, were taken in with ballast water in the Shatt-al-Arab (Salman et al, 1990) or any of the many ports along the Southeast Asian coast, and were released with offloaded ballast outside the port ofİzmir while loading containers. In recent years we have witnessed several cases of alien outbreaks in the Levantine Basin (Goren et al, 2008). The sudden appearance of a population of M. affinis, large enough to be commercially exploited, may be a boon forİzmir Bay's artisanal fishermen, who turned from beach seining (prohibited since 2001) to trammel netting for prawns.…”
Section: Material Results and Discussionmentioning
confidence: 99%
“…The first record of the cardinal fish, Apogon smithi (Kotthaus, 1970) was reported by Golani et al (2008) from the Israel coast of the Mediterranean Sea. The second location record was reported by Goren et al (2008) from the İskenderun Bay, Turkey. Golani et al (2008) and Goren et al (2008) observed this species on sandy and muddy bottoms at depths of 20 -40 m.…”
Section: Introductionmentioning
confidence: 99%
“…Four alien cardinal fish species were reported from the Mediterranean Sea (Haas & Steinitz, 1947;Eryılmaz & Dalyan, 2006;Golani et al, 2008;Goren et al, 2008Goren et al, , 2009a. The first record of the cardinal fish, Apogon smithi (Kotthaus, 1970) was reported by Golani et al (2008) from the Israel coast of the Mediterranean Sea.…”
Section: Introductionmentioning
confidence: 99%